Chicken eggshell as suitable calcium source at home - Brun, Lucas Ricardo Martín (2013)
Aim: Taken into consideration that the deficiency of calcium (Ca) in the diet is a common problem, the aim of this work was to study the chicken eggshell as Ca source at home. It was evaluated: (1) different mechanisms to process eggshells and find an easy way to determine the required amount of Ca at home and; (2) the flavor and the texture for eggshell fortified food. Methods: Chemical and mechanical methods of eggshell processing were evaluated. Changes in flavor and texture were evaluated in volunteers coordinated by a professional chef. Results: A single eggshell contains 2.07 0.18 g of Ca; therefore half an eggshell could provide the amount of Ca needed by adult human beings per day. The best way to use chicken eggshell as Ca dietary supplement is powdered to add to bread, pizza or spaghetti as there were small changes in texture and no changes in flavor.